Analisis Ekonomi terhadap Peran BUMDes dalam Meningkatkan Pendapatan Asli Desa: Studi Data Sekunder - Irawansyah, Irawansyah; Adhar, Adhar; Junaidin, Junaidin; Alfisahrin, Alfisahrin; Pertiwi, Aditiyani Nugraha; Gunawan, Ewan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Village development in Indonesia following Law No. 6 of 2014 positions Village-Owned Enterprises (BUMDes) as a strategic instrument for fiscal independence. This study aims to examine the relationship between BUMDes performance and Village Original Revenue (PADes) and its implications for community welfare, while considering the legal framework as a foundation. The research employs an associative quantitative approach using secondary data, including BUMDes financial reports, PADes realization, and welfare indicators, analyzed through linear regression and correlation. Findings reveal a significant positive relationship between BUMDes performance and PADes (R² = 0.46; p < 0.05), while PADes shows a moderate correlation with community welfare (r = 0.52). A normative legal analysis indicates that although regulations such as Law No. 6/2014 and Government Regulation No. 11/2021 provide strong legitimacy, implementation at the village level still faces technical and administrative challenges. In conclusion, BUMDes significantly contributes to PADes; however, welfare impacts require affirmative policies in PADes allocation and stronger institutional capacity at the village level.